Moderate endurance training prevents doxorubicin-induced in vivo mitochondriopathy and reduces the development of cardiac apoptosis - Ascensao, Antonio; Magalhaes, Jose; Soares, Jose M. C; Ferreira, Rita; Neuparth, Maria J; Marques, Franklim; Oliveira, Paulo J; Duarte, Jose A (American journal of physiology. Heart and circulatory physiology, 2005)
1 Department of Sport Biology, Faculty of Sport Sciences, 2 Department of Biochemistry and Clinical Analysis, Faculty of Pharmacy, and 3 Institute for Molecular and Cell Biology, University of Porto, Porto; and 4 Centre of Neurosciences and Cell Biology, Department of Zoology, University of Coimbra, Coimbra, Portugal Submitted 9 December 2004 ; accepted in final form 19 March 2005 The objective of this work was to test the hypothesis that endurance training may be protective against in vivo doxorubicin (DOX)-induced cardiomyopathy through mitochondria-mediated mechanisms. Forty adult (68 wk old) male Wistar rats were randomly divided into four groups ( n = 10/group): nontrained, nontrained + DOX treatment (20 mg/kg), trained (14 wk of endurance treadmill running, 6090 min/day), and trained + DOX treatment. Mitochondrial respiration, calcium tolerance, oxidative damage, heat shock proteins (HSPs), antioxidant enzyme activity, and apoptosis markers were evaluated. DOX induces mitochondrial respiratory dysfunction, oxidative damage, and histopathological lesions and triggers apoptosis ( P < 0.05, n = 10). However, training limited the decrease in state 3 respiration, respiratory control ratio (RCR), uncoupled respiration, aconitase activity, and protein sulfhydryl content caused by DOX treatment and prevented the increased sensitivity to calcium in nontrained + DOX-treated rats ( P < 0.05, n = 10). Moreover, training inhibited the DOX-induced increase in mitochondrial protein carbonyl groups, malondialdehyde, Bax, Bax-to-Bcl-2 ratio, and tissue caspase-3 activity ( P < 0.05, n = 10). Training also increased by 2-fold the expression of mitochondrial HSP-60 and tissue HSP-70 ( P < 0.05, n = 10) and by 1.5-fold the activity of mitochondrial and cytosolic forms of SOD ( P < 0.05, n = 10). We conclude that endurance training protects heart mitochondrial respiratory function from the toxic effects of DOX, probably by improving mitochondrial and cell defense systems and reducing cell oxidative stress. In addition, endurance training limited the DOX-triggered apoptosis. heart mitochondria; exercise; oxidative phosphorylation Address for reprint requests and other correspondence: A. Ascensão, Dept. of Sport Biology, Faculty of Sport Sciences, Univ. of Porto, Rua Dr. Plácido Costa, 91, 4200-450 Porto, Portugal (E-mail: aascensaoatfcdef.up.pt )